Role of tryptophan degradation in respiratory burst-independent antimicrobial activity of gamma interferon-stimulated human macrophages. - Murray, H W (1989)
To determine whether extracellular tryptophan degradation represents an oxygen-independent antimicrobial mechanism, we examined the effect of exogenous tryptophan on the intracellular antimicrobial activity of gamma interferon (IFN-gamma)-stimulated human macrophages. IFN-gamma readily induced normal monocyte-derived macrophages (MDM) to express indoleamine 2,3-dioxygenase (IDO) activity and stimulated MDM, alveolar macrophages, and oxidatively deficient chronic granulomatous disease MDM to degrade tryptophan. All IFN-gamma-activated, tryptophan-degrading macrophages killed or inhibited Toxoplasma gondii, Chlamydia psittaci, and Leishmania donovani. Although exogenous tryptophan partially reversed this activity, the increases in intracellular replication were variable for normal MDM (T. gondii [5-fold], C. psittaci [3-fold], L. donovani [2-fold]), chronic granulomatous disease MDM (T. gondii [2.5-fold], C. psittaci [5-fold]), and alveolar macrophages (T. gondii [1.5-fold], C. psittaci [1.5-fold]). In addition, IFN-alpha and IFN-beta also stimulated normal MDM to express IDO and degrade tryptophan but failed to induce antimicrobial activity, and IFN-gamma-treated mouse macrophages showed neither IDO activity nor tryptophan degradation but killed T. gondii and L. donovani. These results suggest that while tryptophan depletion contributes to the oxygen-independent antimicrobial effects of the activated human macrophage, in certain cytokine-stimulated cells, tryptophan degradation may be neither sufficient nor required for antimicrobial activity.